Ophthalmomyiasis Externa due to Oestrus ovis Larvae: A Case Report - Jens Schrecker; Rebecca Ahnert (Case Reports in Ophthalmology, 2022)
A 23-year-old female presented with redness, itchiness, tearing, and foreign body sensation in her right eye after spending her holiday in Egypt. Slit lamp examination revealed about 15 mobile, whitish maggots that were microbiologically classified as Oestrus ovis larvae. All parasites could be removed without subsequent complications.